SNPs and taxane toxicity in breast cancer patients. (November 2014) - Bosó, Virginia; Herrero, María José; Santaballa, Ana; Palomar, Laura; Megias, Juan E; de la Cueva, Helena; Rojas, Luis; Marqués, María Remedios; Poveda, José Luis; Montalar, Joaquin; Aliño, Salvador F
Aim: In order to identify genetic variants associated with taxanes toxicity, a panel with 47 SNPs in 20 genes involved in taxane pathways was designed.Patients & methods: Genomic DNA of 113 breast cancer patients was analyzed (70 taking docetaxel, 43 taking paclitaxel).Results: Two SNPs associated with docetaxel toxicity were identified: CYP3A4*1B with infusion-related reactions; and ERCC1 Gln504Lys with mucositis (p ≤ 0.01). Regarding paclitaxel toxicity: CYP2C8 HapC and CYP2C8 rs1934951 were associated with anemia; and ERCC1 Gln504Lys with neuropathy (p ≤ 0.01).Conclusion: Genes involved in DNA repair mechanisms and reactive oxygen species levels influence taxane toxicity in cancer patients treated with chemotherapy schemes not containing platinum. These findings could lead to better treatment selection for breast cancer patients.